Docile Bodies in Chinese Schools: What Defines a Future Postmodern Education? - Li, Yulong (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
As early as the 1990s, educationists, and even some governmental policy makers in China, advocated suzhi (quality) educational reform, aiming to develop creative individuals, and to revamp the exam-oriented and authoritarian education system. However, this suzhi educational reform was not entirely successful, with education in China becoming a hybrid of suzhi coupled with the much-maligned authoritarian and exam-oriented system. I believe that students’ quotidian life at school is governed by a disciplinary power that imposes a hidden curriculum. This essay uses Foucault’s major theories as a conceptualizing framework by examining the control of time, space, and body etc. as technologies of power at Chinese primary and secondary schools. The study concludes by depicting a postmodern future for Chinese students in which they flourish with creativity and innovation.